View Preferences and Tourism Attraction Resources at Mangrove Guraping Tourism Objects, North Oba District, Tidore City, North Maluku Province - Parliansyah, M Rizky; Abubakar, Salim; Sabar, Mesrawaty; Rina, Rina; Subur, Riyadi; Serosero, Rugaya H.; Sunarti, Sunarti; Abubakar, Yuyun; Al Hadad, M. Said; Darlita, Ayu; Nur, D.M.; Nur, Iswan M. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Mangrove forest tourism is a form of tourism activity by traveling around the mangrove forest area and enjoying all the uniqueness contained in it. The choice of a tourist location as a tourist destination is greatly influenced by tourist preferences and ecotourism resources are closely related to attractiveness. Elements of attraction include natural beauty, the abundance of prominent resources, the uniqueness of natural resources, the integrity of natural resources, the choice of recreational activities, and the diversity of natural resources. The aims of this research are: determining tourist view preferences and determining tourist attraction resources at the Guraping mangrove ecotourism object, North Oba District, Tidore Islands City. The data collection process includes field observations, distributing questionnaires, interviews, tourist view preferences and potential tourism resources. The research results showed that the preference for tourist views of the Guraping mangrove tourist attraction was that the mangrove forest landscape obtained the highest SBE value, while the village landscape obtained the lowest SBE value. Potential ecotourism attraction resources that can be developed include mangrove forests with fauna/diversity, bays and beaches, fish ponds and villages with social culture.